Recent advances in foodborne pathogen detection using photoelectrochemical biosensors: from photoactive material to sensing strategy - Dong, Xiuxiu; Huang, Ao; He, Lilong; Cai, Chaoyang; You, Tianyan (Frontiers in Sustainable Food Systems, 2024)
Rapid assessment and prevention of diseases caused by foodborne pathogens is one of the existing food safety regulatory issues faced by various countries, and it has received wide attention from all sectors of society. When the content of foodborne pathogens in food is higher than the limit standard and spreads in a certain way, it can cause disease outbreaks, which seriously threaten human health or life safety. Developing a novel method to detect foodborne pathogens accurately and rapidly is significant. Because of the limitations of complex steps, time-consuming, low sensitivity or poor selectivity of commonly used methods, a photoelectrochemical (PEC) biosensor based on electrochemistry is developed. Its advantages include a low background signal, fast response and simple operation. It also has broad application prospects for sensing, which has attracted wide attention. However, an organised summary of the latest PEC biosensors for foodborne pathogen sensing has not been reported. Therefore, this review introduces the recent advances in foodborne pathogen detection using PEC biosensors as follows: (i) the construction of PEC biosensors, (ii) the research status of PEC biosensors for the detection of foodborne pathogens and (iii) the direction of future development in this field. Hopefully, the study will provide some insight into developing more mature biosensing strategies to meet the practical needs of foodborne pathogen surveillance.